Feminist Therapy Islam Sebagai Alternatif Menangani Korban Kekerasan dalam Rumah Tangga - Ade Nurzaman (Fakultas Dakwah UIN Prof. K.H. Saifuddin Zuhri, 2017)
Domestic Violence (KDRT) both in quantity and quality tends to increase, this can be caused by several things. First, public awareness of human rights has become part of people’s lives. Second, the number of institutions that care enough about the phenomenon of domestic violence so as to be able to report the numbers of violence that occurred. So far, the handling of domestic violence is still limited to the victims of violence. The approach of counseling theory that is considered relevant to cases of domestic violence is Islamic feminist therapy (Islamic feminist therapy). The concept built in feminist theory uses a system perspective integrated with Islamic psychology, meaning that the process of counseling intervention is not only to the individual but also environment to ensure the settlement of the root of the problem and even a spiritual and religious touch. The ability of counselors to empower individuals or communities within the victim’s environment is a skill that must be sharpened by counselors who use feminist therapy. This theory is based on three principles: First, the personal is political; Second, egalitarian relationship; and Third, the valuing perspective. These concepts that become pillars of feminist therapy and weighed with religion become important indicators in determining the ability of counselors in helping accompany victims of domestic violence. Angka Kekerasan Dalam Rumah Tangga (KDRT) secara kuantitas maupun kualitas cenderung meningkat, disebabkan oleh beberapa hal. Pertama, kesadaran masyarakat terhadap hak-hak asasi sudah menjadi bagian kehidupan masyarakat. Kedua, banyaknya lembaga yang cukup peduli pada fenomena KDRT sehingga mampu melaporkan angka- angka kekerasan yang terjadi. Selama ini penanganan KDRT masih sebatas pada korban kekerasan. Pendekatan teori konseling yang dianggap relevan dengan kasus kekerasan dalam rumah tangga adalah feminis terapi islam (Islamic feminist therapy). Konsep yang dibangun dalam teori feminis memakai perspektif sistem yang diintegrasikan dengan psikologi Islam, artinya proses intervensi konseling tidak hanya kepada individu tetapi lingkungan individu ikut diberi perlakuan untuk menjamin penyelesaian akar masalah bahkan ada sentuhan spiritual dan religius. Kemampuan konselor untuk memberdayakan individu/masyarakat di lingkungan korban merupakan kemampuan yang harus diasah oleh konselor yang memakai terapi feminis. Teori ini didasari pada prinsip, yaitu; Pertama, the personal is political; Kedua, egalitarian relationship; dan Ketiga, the valuing perspective. Ketiga konsep yang menjadi pilar terapi feminis dan ditimbang dengan agama menjadi indikator penting dalam menentukan kemampuan konselor dalam membantu mendampingi korban KDRT.